The Determination for Cadmium in Biological Materials - Young, Ronald E. (My University, 1974)
With the increasing concern about pollution the need has arisen for accurate trace analysis of hazardous or toxic trace elements such as cadmium. While the modern analytical chemist has at his disposal a great many different techniques for analysis, surveys of inter-laboratory analyses have often produced serious discrepancies among results done by different methods and/or workers. The purpose of this thesis will be to review the different methods for trace analysis of cadmium in biological samples and to experimentally compare two of these, atomic-absorption spectrometry and neutron-activation analysis.
Keywords: cadmium, biological materials, pollution, hazardous, atomic-absorption, neutron-activation